Ilha dos números inteiros: jogos educativos e materiais manipulativos no ensino e aprendizagem de números inteiros - Oliveira, Luis Antonio Alcantara (2025)
The research investigates the contribution of manipulative materials, specifically educational games, to the teaching and learning of integers—a topic in which many students often face significant difficulties. The study analyzed whether the use of games improved students' understanding and performance by adopting a methodology based on practical challenges. Grounded in Piaget's constructivist theory, the work highlights the importance of the individual's active interaction with the environment for effective learning. The project was designed with the goal of proposing a treasure hunt adventure for students, called Island of Integers. A treasure map was introduced, and the adventure is about to begin. The games were developed to stimulate logical reasoning, problem-solving, interaction, and healthy competition among participants, providing a playful and contextualized experience of mathematical concepts.